Macro- and micro-nutrient uptake pattern and their use efficiencies for maize (Zea mays) in maize-wheat (Triticum aestivum) cropping system under nutrient omissions - JOSHI, EKTA; VYAS, A K; DHAR, SHIVA; DASS, ANCHAL; PRAJAPATI, KAILASH; JINGER, DINESH; SASODE, D S (The Indian Journal of Agricultural Sciences, 2020)
A 2-year (2012 and 2013) field experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi to assess the effect of omitted nutrients on nutrient concentration and uptake and (nutrient use efficiency) NUE for maize (Zea mays L.) in maize–wheat (Triticum aestivum L.) cropping system. The STCR-based application of nutrients was more rewarding in terms of improved concentrations, uptakes and better NUE of macro (N, P, K) and micro-nutrients (Zn) in maize. This treatment increased the total uptake of N, P and K by 14.9, 12.5 and 9.3 %, respectively, over recommended rates of NPKZn application. The continuous omission of P resulted in 13.7, 11.5 and 4.7 % reduction in total uptake of N, P and K, respectively. Similar to P, omitting K to both crops continuously also resulted in reduction of total uptake of N, P, K, Zn by 22.1, 13.6, 23.4, 1.9, respectively. Omitting Zn to both maize and wheat crop during 2012 and 2013 did not influence total nutrient uptake significantly. Omitting P and K also exhibited reduced agronomic efficiency and apparent recovery. Balanced application of NPK to preceding wheat crop resulted in higher uptake of N, P and K by maize compared to absolute control and imbalanced application of N, NP or NKZn directly to maize crop during experimentation. Omitting N, P or K to maize resulted in reduction in NUE and uptake in maize during second study year.